Evaluation Of Online Learning Implementation In The Middle Of The Covid-19 Corona Virus Pandemic In Palangka Raya Sma Penjas Subjects - Yosita wisman; Indrianto Arif Ramadhana; Jeff Agung Perdana (Universitas Bengkulu, 2021)
Corona Virus Disease (Covid-19) has altered the way of live of worldwide society including in Indonesia. Education has become one of the affected sectors ruquiring a change on its system from direct to distance teaching through online platforms. This study aims to describe the effectiveness of online learning during Covid-19 in Senior High School Palangka Raya on 2019/2020 period. This descriptive quantitative used in this study was a survey methods take by online platfrom and analyzed descriptively. The result showed that online Physical Education Health and Sport are effectively implemented. The most convenient appplication used by students is google classroom with indiviual task and multiple choice as easier task to understood. The lack of this online methods faced by sttudents are internet network problems